A novel HLA‐B allele, HLA‐B*35:269. (2nd February 2016) - Zhu, X.; Yang, T.; Tan, R.; Su, P.; Li, Z.
Abstract : HLA‐B*35:269 differs from HLA‐B*35:01:01:01, by a single synonymous nucleotide at position 103.